Ammosamide D, An Oxidatively Ring Opened Ammosamide Analog from a Marine-derived Streptomyces variabilis - Pan, Ende (2012)
[Image: see text] Ammosamide D (1), an oxidized analog of the ammosamide family, was isolated from a marine-derived Streptomyces variabilis. Pyrroloquinoline containing alkaloids are a growing class of natural products, with 1 being the first example of an oxidized analog resulting in a 5,6-dioxo-5,6-dihydroquinoline ring system. Attempts at chemical conversion of ammosamide B to ammosamide D revealed that a strong chemical oxidant is required. Ammosamide D has modest cytotoxicity to the MIA PaCa-2 pancreatic cancer cell line.